2005
DOI: 10.1002/masy.200551140
|View full text |Cite
|
Sign up to set email alerts
|

FT‐IR Spectroscopy and Hydrogen Bonding Interactions in Poly(styrene‐co‐methacrylic acid)/Poly(styrene‐co‐4‐vinyl pyridine) Blends

Abstract: Summary: This contribution reports on a FT-IR study of the hydrogen bonding interactions within blends of different ratios of poly(styrene-co-methacrylic acid) containing 15 mol% of methacrylic acid PSMA-15 and poly(styrene-co-4-vinylpyridine) containing 15 mol% of 4-vinylpyridine PS4VP-15. Equilibrium constants describing both the self-association K 2 and inter-association K A in the (75:25) blend of poly-(styrene-co-methacrylic acid) containing 12 mol% of methacrylic acid PSMA-12 with poly(styrene-co-4-vinyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 18 publications
4
14
0
Order By: Relevance
“…In previous studies,18, 19 we reported that PPO is totally miscible with poly(styrene‐ co ‐methacrylic acid) (PSMA) containing 7.8 mol % methacrylic acid (PSMA‐7.8, where the number following the hyphen refers to the percentage methacrylic acid in the polymer) and with blends of PSMA‐12 containing less than 67 wt % PPO. As we have also confirmed qualitatively and quantitatively by Fourier transform infrared (FTIR) spectroscopy,20 the miscibility of PSMA‐12/poly(styrene‐ co ‐4‐vinylpyridine) (PS4VP) containing 22% 4‐vinylpyridine (PS4VP‐22, where the number following the hyphen refers to the percentage 4VP in the polymer) is due to the presence of hydrogen‐bonding interactions.…”
Section: Introductionsupporting
confidence: 67%
“…In previous studies,18, 19 we reported that PPO is totally miscible with poly(styrene‐ co ‐methacrylic acid) (PSMA) containing 7.8 mol % methacrylic acid (PSMA‐7.8, where the number following the hyphen refers to the percentage methacrylic acid in the polymer) and with blends of PSMA‐12 containing less than 67 wt % PPO. As we have also confirmed qualitatively and quantitatively by Fourier transform infrared (FTIR) spectroscopy,20 the miscibility of PSMA‐12/poly(styrene‐ co ‐4‐vinylpyridine) (PS4VP) containing 22% 4‐vinylpyridine (PS4VP‐22, where the number following the hyphen refers to the percentage 4VP in the polymer) is due to the presence of hydrogen‐bonding interactions.…”
Section: Introductionsupporting
confidence: 67%
“…In common case both the peak position and shape of the C v O stretching are very sensitive to local environment. [23][24][25][26][27] In our case, three different types of hydrogen bonds can occur as shown in schematic in Fig. 24 Formation of one hydrogen bond can cause this frequency redshifts by 20-25 cm −1 .…”
Section: Resultsmentioning
confidence: 98%
“…In fact, the value for the autoassociation constant through carbonyl groups in PS-MAA copolymers at 25 8C is 9.2 or 22. [18] It seems that our systems display low hydrogen bond interactions (moderate at most), and therefore a single set of parameters has been used to evaluate the…”
Section: Discussionmentioning
confidence: 99%